2021
DOI: 10.18502/kss.v5i6.9224
|View full text |Cite
|
Sign up to set email alerts
|

Computer Based Test Using the Fisher-Yates Shuffle and Smith Waterman Algorithm

Abstract: Tests are used to determine a person’s level of understanding of a subject. The inhibiting factors in tests are less varied questions, questions with insufficient difficulty, subjective assessments, and the length of time in their correction. This research aimed to develop a Computer Based Test (CBT) application. The type of questions in this CBT are multiple choice and essays. This CBT employs categorization of questions, randomization of the questions, and automatic assessment. Questions were categorized man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Proses ini terus diulangi hingga semua elemen telah ditukar. Selain itu, algoritma ini juga digunakan untuk menghasilkan permutasi acak dari himpunan terhingga [8].…”
Section: Algoritma Fisher-yates Shuffleunclassified
“…Proses ini terus diulangi hingga semua elemen telah ditukar. Selain itu, algoritma ini juga digunakan untuk menghasilkan permutasi acak dari himpunan terhingga [8].…”
Section: Algoritma Fisher-yates Shuffleunclassified
“…This algorithm is a technique for randomizing, such as randomizing the arrangement of puzzles in games [9], or in multiplayer games to randomly bring up enemy objects [10]. Several other studies that use the Fisher-Yates algorithm such as [3], [5], [11], [12], and [13] giving good results in randomizing exam questions. In another research by [14] Fisher-Yates method is unbiased and used because this method has a good randomization strategy and is suitable for numerical randomization with better execution time than the naive shuffle algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be noted that the execution used to generate random numbers, exchange, and subtraction entirely runs on space or the same place, and then do a loop or repeated n times. Therefore, it can be concluded that the Fisher-Yates Shuffle algorithm has complexity linear time or time complexity O(n) and space complexity which is more efficient because it does not require extra space and all steps are performed in the same place or array so that obtaining space complexity is constant O(1) [17]. The following step is a randomization step performed on the Fisher-Yates Shuffle algorithm with the modern method.…”
Section: B Fisher Yates Shuffle Algorithmmentioning
confidence: 99%